Formatação de sistemas de franquias: da propriedade intelectual à transferência de tecnologia - Amaral, Aline de Góes Lima (2020)
Expansion through franchises is a strategy used by several types of companies. Despite the maturity of the techniques used and the free growth of the sector, in Brazil, there are still gaps in academic studies and in the practices that involve the protection and management of the intellectual property in the structuring of franchises. The current franchise legislation, recently published, reinforces the need for a more in-depth look at the intangible assets involved in this business model. The present work aims to create a franchise structuring model that contemplates the best management practices, incorporating an approach focused on the protection and management of intangible assets. An applied social research was carried out using exploratory, bibliographic and documentary survey, as a methodological approach with a qualitative analysis of the data. The process modeling technique BPM (Business Process Management) was used for the structuring of the system, following the pattern of symbols of BPMN (Business Process Model and Notation). As a result, the work presents a structuring of a franchise system that goes beyond the use of conventional instruments, working with an approach focused on the identification, protection, and management of intangible assets, which are important for the franchise and which often define the competitive advantage of the company. In addition, a list of recommendations is also presented that serve to map and protect franchisors' intangible assets. It is concluded that, in practice, the implementation of these strategies will avoid surprises, concerns, and instabilities regarding the risks involved in the transfer of technology, thus contributing as one of the sources of sustainable competitive advantage for the entire franchise system.